Financial Intermediation and Aggregate Demand: A Sufficient Statistics Approach - Chiang, Yu-Ting; Zoch, Piotr (Review of Economic Studies, 2026)
Abstract We show that the financial sector’s asset supply elasticities are sufficient statistics summarizing its macroeconomic effects for a large class of financial frictions. These elasticities are crucial for a wide range of policy questions, ranging from the size of fiscal multipliers to the relative effectiveness of asset purchases targeting the financial sector versus tax cuts targeting households. Workhorse macroeconomic models imply different values of these elasticities, generating output responses to policies that differ by orders of magnitude. We construct empirical measures of these elasticities and evaluate their policy implications in a quantitative model with household heterogeneity and illiquidity.